What is ‘agency’ in torture and trauma recovery? An inquiry into the properties and explanations of the concept of agency and it’s impacts - Wyatt, Susan (Torture Journal, 2023)
The global ontology of survivor-led movements provides a useful reflection on conceptual frameworks and pathways for effective and strategic mechanisms for facilitating ’agency’ within the spectrum of torture rehabilitation. This paper aims to provide a theoretical overview and analysis of the concepts, working frameworks, implementation methods and outcomes of survivor-led initiatives. The terminologies and meanings of survivor engagement are unpacked, highlighting the assumptions and implications for how services are designed, delivered and evaluated. This paper deliberately straddles multiple thematic fields to showcase and learn from other successful movements, and invites you as the reader into this discourse of inquiry now from the perspective of torture treatment services. This paper deep dives into survivor-led concepts, opening the plethora of adaptations available and encouraged. It looks firstly at the broader contexts that provide commonality and structure for concepts around power, empowerment or agency, before then exploring particularities from different contexts to enable the perspective of the ’differientiated whole’ in Survivor Engagement programming. It concludes with thematic areas bearing implications for practice going forwards.